PENERAPAN REWARD DALAM PEMBELAJARAN DI MTsS BABUN NAJAH BANDA ACEH - Qurrata Akyuni (AZKIA : Jurnal Aktualisasi Pendidikan Islam, 2022)
Reward is one of the key determinants of student attention. Teachers can use various ways so that students pay attention to ongoing learning. Application of good and appropriate rewards will have a good impact on increasing student achievement in everyday learning, but conversely if the application of rewards that are incorrect and excessive will have a negative effect on students which results in student achievement. This is what makes the application of rewards in learning at MTsS Babun Najah Banda Aceh very necessary. This study aims to describe the form of reward and how it is given in learning at MTsS Babun Najah Banda Aceh. The type of research used is descriptive qualitative. The results of the study explain that teachers play an active role in implementing rewards for their students in various forms including in the form of gifts, grades, rankings and symbols, activities and gestural forms. The method used in implementing the reward is directly and indirectly.